2011
DOI: 10.1016/j.jml.2011.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Scalar reference, contrast and discourse: Separating effects of linguistic discourse from availability of the referent

Abstract: Listeners expect that a definite noun phrase with a pre-nominal scalar adjective (e.g., the big …) will refer to an entity that is part of a set of objects contrasting on the scalar dimension, e.g., size (Sedivy, Tanenhaus, Chambers & Carlson, 1999). Two visual world experiments demonstrate that uttering a referring expression with a scalar adjective makes all members of the relevant contrast set more salient in the discourse model, facilitating subsequent reference to other members of that contrast set. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 56 publications
3
22
0
Order By: Relevance
“…Our results are also in line with the study of Wolter et al (2011) in which they demonstrated separate effects of linguistic and non-linguistic information in reference resolution. They showed that the mention of a scalar adjective in the description of an object (e.g., a tall candle) facilitated subsequent reference to objects that were contrasted with the adjective (e.g., a small candle) whereas no such facilitation occured in cases in which participants attended to the same objects but no scalar adjectives were used in the description.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are also in line with the study of Wolter et al (2011) in which they demonstrated separate effects of linguistic and non-linguistic information in reference resolution. They showed that the mention of a scalar adjective in the description of an object (e.g., a tall candle) facilitated subsequent reference to objects that were contrasted with the adjective (e.g., a small candle) whereas no such facilitation occured in cases in which participants attended to the same objects but no scalar adjectives were used in the description.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, Wolter, Skovbroten Gorman, and Tanenhaus (2011) demonstrated that in language comprehension, linguistic and non-linguistic information made separate contributions to reference resolution. Their participants moved objects in a visual display according to instructions while their eye movements were recorded.…”
Section: Is Anaphoric Reference Cooperative?mentioning
confidence: 99%
“…In the AND condition, there is no contrast between the two concepts because they are both non-negated, but in the NOT condition, the negation of Noun2 creates an inherent contrast between the two concepts (i.e., one concept is selected and the other is not). Research has shown that when one member of a contrast set is mentioned, the other member of the contrast set is activated as well (Wolter et al, 2011). Therefore, when the negation increases the activation of Noun2 as hypothesized, it may also be increasing the activation of the contrasted Noun1, causing a similar increase in references relative to the AND condition.…”
Section: Discussionmentioning
confidence: 85%
“…As previously discussed, this effect may be the result of the contrast implicit in the NOT condition and made explicit by the word but. When one item in a contrastive set increases in activation, this activation also spreads to the other item in the set (Wolter et al, 2011). Therefore, when Noun2 increases in activation, either through additional processing required to comprehend non-licensed negation (Experiments 1a and 1b) or through repetition of the concept (Experiment 2), the activation level of Noun1 also increases.…”
Section: Discussionmentioning
confidence: 96%
“…Assuming that the extent to which competitors are fixated reflects their degree of activation in the speaker s mind, as implicitly assumed in eye-tracking studies (Huettig & Hartsuiker, 2008;Wolter, Gorman, & Tanenhaus, 2011), we would expect relatively fewer fixations on agents in animate-head passives compared to inanimate-head passives, due to similarity-based mechanisms in the former but not the latter. That is, in competitive situations (animate-head targets), the agent is relatively less activated due to interference with the target, compared to non-competitive situations (inanimate-head targets), although it should still be more active than unrelated entities, as utterance-relevant characters are.…”
Section: Discussionmentioning
confidence: 93%